Multiple Reversible MR Signal Changes Caused by Epstein-Barr Virus Encephalitis - Hagemann, G.; Mentzel, H.-J.; Weisser, H.; Kunze, A.; Terborg, C. (American Journal of Neuroradiology, 2006)
SUMMARY: This report presents the imaging findings of an unusual case of Epstein-Barr virus (EBV) encephalitis. A young man presented with a short-lasting history of febrile infection, neuropsychologic deficits, ataxia, and seizures. MR imaging revealed fully reversible signal intensities (T2, diffusion-weighted imaging with a decreased apparent diffusion coefficient) in the splenium of the corpus callosum and both posterior hemispheres. EBV infection must be added to the list of differential diagnoses of (reversible) splenial lesions.